VOLATILITAS HARGA KEDELAI DAN INTEGRASI PASAR KEDELAI SEBELUM DAN SESUDAH PANDEMI COVID 19 - Syaima; Fariyanti, Anna; Rifin, Amzul (Jurnal Sosial Humaniora, 2022)
Soybean is one of the main food commodity in Indonesia beside rice and corn, so it is necessary to maintain price stabilization. This study aims analyze the volatility of soybean prices and the integration of Indonesian and international soybean markets before and after the COVID-19 pandemic.The ARCH/GARCH model is used in the analysis of soybean price volatility and the VAR/VECM model is used to analyze the market integration between the Indonesian soybean market and the international market. The result of research show that local retail soybean price have a higher price volatility than international soybean price and imported soybean price. Soybean price volatility after the COVID-19 pandemic also showed a higher level of price volatility compared to conditions before the COVID-19 pandemic. Meanwhile, the result of market integration show that there is market integration between the Indonesian soybean market and the American market, and the impact of the COVID-19 pandemic on the formation of local soybean prices at the producer level.